Cinnamon Polyphenol Extract Inhibits Hyperlipidemia and Inflammation by Modulation of Transcription Factors in High-Fat Diet-Fed Rats - Tuzcu, Zeynep; Orhan, Cemal; Şahin, Nurhan; Juturu, Vijaya; Şahin, Kazım (Hindawi Ltd, 2017)
We evaluated the effects of cinnamon polyphenol extract on hepatic transcription factors expressions including SREBP-1c and LXR-alpha in rats fed high fat diet (HFD). Twenty-eight Wistar rats were allocated into four groups: (i) normal control: animals fed with normal chow; (ii) cinnamon: animals supplemented with cinnamon polyphenol; (iii) HFD: animals fed a high-fat diet; and (iv) HFD 1 cinnamon: animals fed a high-fat diet and treated with cinnamon polyphenol. Obesity was linked to hyperglycemia, hyperlipidemia, and oxidative stress as imitated by elevated serum glucose, lipid profile, and serum and liver malondialdehyde (MDA) concentrations. Cinnamon polyphenol decreased body weight, visceral fat, liver weight and serum glucose and insulin concentrations, liver antioxidant enzymes, and lipid profile (P < 0.05) and reduced serum and liver MDA concentration compared to HFD rats (P < 0.05). Cinnamon polyphenol also suppressed the hepatic SREBP-1c, LXR-alpha, ACLY, FAS, and NF-kappa B p65 expressions and enhanced the PPAR-alpha, IRS-1, Nrf2, and HO-1 expressions in the HFD rat livers (P < 0.05). In conclusion, cinnamon polyphenol reduces the hyperlipidemia, inflammation, and oxidative stress through activating transcription factors and antioxidative defense signaling pathway in HFD rat liver.
Keywords: Insulin-Resistance; Oxidative Stress; Antioxidant Response; Improves Glucose; Induced Obesity; Bark Extract; Kappa-B; Receptor; Liver; Chromium